Differential impact of tax incentive mechanisms on financial performance of listed oil and gas companies in Nigeria - NURUDEEN, ABDULFATAI OLANREWAJU; Ogunbowale, Funmi Racheal (Manajemen dan Bisnis, 2025)
This study examines the effect of tax incentives on the financial performance of listed oil and gas firms in Nigeria. Using panel data from nine firms on the Nigerian Exchange Group (2005–2024) and a Fixed Effects Model guided by the Hausman test, the analysis focuses on Investment Tax Allowance (ITA), Tax Exemption (TEX), and Tax Credit (TCR) as proxies for tax incentives, with Return on Assets (ROA) as the performance measure. Results show that ITA has a significant positive effect on ROA, demonstrating that investment-focused tax relief enhances asset efficiency. Conversely, TEX and TCR display no significant impact, suggesting their limited role in improving profitability. Among control variables, firm size negatively affects ROA, while firm age exerts a positive effect. These findings are consistent with Ibn Khaldun’s Theory of Taxation, which emphasizes the role of moderate taxation in stimulating economic activity. The study concludes that ITA is the most effective tax incentive for strengthening financial performance in the Nigerian oil and gas sector. It recommends continued implementation of ITA, strategic use of tax credits for reinvestment, and broader adoption of exemptions to reduce fiscal burdens.